New vectors for epitope tagging and gene disruption in Schizosaccharomyces pombe - Gadaleta, Mariana C. (2013)
We describe a series of new vectors for PCR-based epitope tagging and gene disruption in the fission yeast Schizosaccharomyces pombe, an exceptional model organism for the study of cellular processes. The vectors are designed for amplification of gene-targeting DNA cassettes and integration into specific genetic loci, allowing expression of proteins fused to 12 tandem copies of the Pk (V5) epitope or 5 tandem copies of the FLAG epitope with a glycine linker. These vectors are available with various antibiotic or nutritional markers and are useful for protein studies using biochemical and cell biological methods. We also describe new vectors for fluorescent protein-tagging and gene disruption using ura4MX6, LEU2MX6, and his3MX6 selection markers, allowing researchers in the S. pombe community to disrupt genes and manipulate genomic loci using primer sets already available for the widely used pFA6a-MX6 system. Our new vectors may also be useful for gene manipulation in Saccharomyces cerevisiae. METHOD SUMMARY: Our 12Pk-tagging vectors for genomic integration significantly improve the sensitivity of protein detection by Western blotting. We also describe genomic 5FLAG-tagging vectors with a glycine linker, which allows flexibility between the epitope and the protein, enhancing immunoprecipitation efficiency. This report also describes vectors for fluorescent-tagging and gene deletion useful in S. pombe.